2017
DOI: 10.3906/bot-1607-48
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphological studies on the genus Lotus L. (Fabaceae: Loteae) from Egypt

Abstract: Lotus is a taxonomically difficult genus. No worldwide taxonomic studies for the whole genus have been produced since the monograph of Brand (1898). A comprehensive taxonomic revision of the genus is needed (Degtjareva et al., 2006). In Egypt, Lotus L. is represented by 18 taxa (Boulos, 2009). The species of Lotus constitute complexes of closely related groups with similar vegetative characters, including seasonal polymorphisms (Heyn, 1970), and it is difficult to distinguish among the species (Ojeda et al., 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In many genera of Lamiaceae, the trichome morphology is very useful for the classification of all taxonomic levels (Marin et al 1994;Navarro and El Oualidi 2000;Moon et al 2009;Salmaki et al 2009;Ecevit-Genç et al 2015, 2017.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In many genera of Lamiaceae, the trichome morphology is very useful for the classification of all taxonomic levels (Marin et al 1994;Navarro and El Oualidi 2000;Moon et al 2009;Salmaki et al 2009;Ecevit-Genç et al 2015, 2017.…”
mentioning
confidence: 99%
“…Plant trichomes are important to descriptive and experimental botanists and data about them and their indumenta are routinely included in many studies. Many authors, such as Behnke (1984); Navarro and El Oualidi (2000); Beyrouthy et al (2009); Moon et al (2009); Kaya et al 2012;Khalik and Hassan (2012); Osman (2012); Ecevit-Genç et al (2017);Genç et al (2017); Zareh et al (2017) emphasize the importance of trichomes in taxonomy.…”
mentioning
confidence: 99%
“…The taxonomy of Lotus is intricate and requires an inclusive taxonomic audit of the genus (Degtjareva et al, 2011). Also, Zareh et al (2017) stated that the anticlinal wall cells varied among the studied Lotus edulis L, Lotus ornithopodioides L., Tetragonolobus purpureus Moench, Medicago laciniata (L.) Mill., Gard. Dict., M.orbicularis (L.) Bart., M.turbinata (L.) All, M.polymorpha L., Ononis vaginalis Vahl, Lathyrus aphaca L., Vicia sativa L., V. peregrine L., and V. tetrasperma (L.) Schreb.…”
Section: Discussionmentioning
confidence: 99%
“…edulis, whereas, Tetragonolobus purpureus the pod inflated, 5-8 mm diam., and the margins were bordered by 4 conspicuous undulate wings. Arambarri (2000) and Zareh et al (2017) stated that the seed coat sculpture exhibited by the genus Lotus was reticulate, rugose, verrucate, and sulcate. These characteristics can serve as prognosis characters of the Lotus species-genus.…”
Section: Discussionmentioning
confidence: 99%
“…Various works have shown that the microcharacters of seed coat, anatomical features and pollen grain features in Leguminosae can be used as diagnostic characters at generic, specific and even at infraspecific levels. Seed morphology and structure in the Leguminosae has been the base of numerous studies (Gunn, 1972;Ignacimuthu & Babu, 1985;Abd El-Gawad et al (1989); Hosni & Karemy 1993, Abou-El-Enain & Loutfy 1999, El Karemy & Hosni 1999, Abou-El-Enain et al 2007Nyola & Sharma, 2009;Özbek et al 2014;Zareh et al 2017;Khandani et al 2016;Abid et al 2018) In Egypt Melilotus is represented by seven species (El-Hadidi & Fayed 1994/95;Boulos 1995Boulos , 1999Boulos , 2009, while Täckholm (1974) recorded only six species of Melilotus. She recorded two varieties within the multiform species M. indicus namely: var.…”
Section: Introductionmentioning
confidence: 99%